2020
DOI: 10.1016/j.acalib.2019.102095
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility Best Practices, Procedures, and Policies in Northwest United States Academic Libraries

Abstract: Academic libraries are responsible for providing accessible copies of collection materials to individuals facing a variety of accessibility needs. Accessibility needs differ from user to user, often making each request an individualized service. However, do academic libraries have a responsibility to embrace a Universal Design for Learning approach to their acquisitions process? Do academic library workers need to establish policies as part of the procurement process? This research surveyed academic libraries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Of the 16 participants (representing various institutions), 90 percent reported that accessibility impacted their acquisitions decision-making in some way, but only about 20 percent said that their library or institution had a policy document or written guidelines about accessibility in purchasing. 14 Most participants also indicated that their institutions did not have room in their budgets to adequately support accessibility training and resources at the library. Only 40 percent said that they had participated in the accessibility training offered at their colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the 16 participants (representing various institutions), 90 percent reported that accessibility impacted their acquisitions decision-making in some way, but only about 20 percent said that their library or institution had a policy document or written guidelines about accessibility in purchasing. 14 Most participants also indicated that their institutions did not have room in their budgets to adequately support accessibility training and resources at the library. Only 40 percent said that they had participated in the accessibility training offered at their colleges and universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The library services for PWDs policy was enforced by ALA states that libraries should work towards facilitating their full participation in society by implementing the Universal Design principles of perceivable, operable, understandable, and robustness. The use of universal design techniques can guarantee that library policy, resources, and services satisfy the needs of all individuals (Peacock & Vecchione, 2020). Improved accessibility of physical and website architecture, providing materials in multiple formats, developing assistive technology resources, and training library staff on effective ways to interact with PWDs are just a few of the UD applications described by library literature.…”
Section: Information Services To Persons With Disabilitiesmentioning
confidence: 99%
“…He found that policies around digitization, electronic resources collections, among others, fall noticeably short of supporting an accessible environment. Peacock and Vecchione (2020) found in their research on academic libraries that they often lacked a comprehensive policy to facilitate the needs of persons with disabilities.…”
Section: Analyzing and Comparing Policies Codes Or Guidelinesmentioning
confidence: 99%